KEJADIAN DRY EYE SYNDROME PASIEN PASCA OPERASI KATARAK METODE FAKOEMULSIFIKASI DI RUMAH SAKIT ISLAM (RSI) SITI RAHMAH PADANG TAHUN 2025 - Tangguh Ariwibawa; Rosmaini Rosmaini; Naima Lassie (Yayasan Nusantara Hasana Berdikari, 2026)
This study aimed to determine the incidence of DES among patients who underwent phacoemulsification cataract surgery at RSI Siti Rahmah Padang in 2025. This study aimed to determine the incidence of DES among patients who underwent phacoemulsification cataract surgery at RSI Siti Rahmah Padang in 2025. This study used a descriptive observational method with a cross-sectional design. Data were collected from both primary and secondary sources. Bottom of FormThe study population included adult patients diagnosed with DES after phacoemulsification cataract surgery. Participants were selected using sequential sampling based on predefined inclusion and exclusion criteria, resulting in a total sample of 58 patients. The highest incidence of DES was observed among patients aged 60–74 years (60.3%), females (60.3%), and those primarily engaged in indoor activities (62.1%). Unilateral DES was the most common presentation, affecting 60.3% of patients. Based on postoperative duration, DES occurred most frequently within 1–3 months after surgery, accounting for 70.7% of cases. Regarding severity, moderate DES was the predominant category, affecting 48.3% of patients. Nearly all patients (98.3%) received artificial tears as treatment. ES following phacoemulsification cataract surgery at RSI Siti Rahmah Padang in 2025 was most frequently found in elderly patients aged 60–74 years, females, individuals with indoor activities, and those experiencing unilateral DES within 1–3 months after surgery. Moderate DES was the most common severity level, and almost all patients were treated with artificial tears therapy.